POLITIK HUKUM PEMBENTUKAN DAERAH OTONOM: ANTARA ASPIRASI LOKAL DAN KEPENTINGAN ELIT POLITIK - Wiguna, Teguh Setia; Aprilianti, Ajeng; Dewi, Anisya Auriana; Ramdani, Fahmi Ali (Universitas Kapuas, 2025)
The policy of establishing new autonomous regions (DOB) in Indonesia is normatively aimed at improving public services and enhancing community welfare. However, in practice, the process is often controlled by the political interests of elites at both the central and regional levels, who exploit the issue of regional expansion as a tool for negotiating power, positions, and resources. Although the expansion is often claimed to be a response to local aspirations, many of these initiatives do not show significant impacts on community welfare and instead give rise to various problems, such as conflicts of interest, manipulation of the political process, and horizontal tensions within the community. The effectiveness of regional expansion is highly determined by the cohesion and understanding among local political elites; when fragmentation occurs among them, the expansion process tends to experience stagnation or even prolonged conflicts. Therefore, a critical study of the legal politics of DOB expansion becomes important to ensure that the policy does not merely serve the interests of a handful of elites, but truly reflects the aspirations and needs of the broader community.